The Relationship between Hypertension and Kidney Stone Formation: Insights from a Cross-Sectional Study - Noori Mahmood, Sarwar; Othman Abdullah , Lizan; Jamal Mohammad, Shifana (Hammurabi Journal of Medical Sciences, 2026)
Background: Urolithiasis and hypertension are common chronic diseases that occur in combination with some metabolic, vascular similarities. The evidence is lacking on the link between these two conditions in Middle Eastern populations where climatic and dietary factors may affect stone risk. Objectives: To assess the relationship between HTN and urolithiasis, and to determine metabolic and lifestyle factors that are independently associated with kidney stone formation in an adult population in the Kurdistan Region of Iraq. Materials and Methods: A cross-sectional analytical study was applied on 364 subjects (aged ≥30 years) visited the urology clinic at Sulaymaniyah city from February to August 2025. Urolithiasis was established with ultrasonography and/or computed tomography. Hypertension was characterized by blood pressure reading, clinical diagnosis or antihypertensive medication. Demographic, metabolic and lifestyle information was obtained. Categorical data were compared between groups using chi-square tests, and independant predictors were determined by binary logistic regression. Results: The prevalence of urolithiasis was significantly greater in the hypertensive group than in normotensives (65.2% vs 47.3%; p = 0.001). Compared to normotensive participants, hypertensive subjects had higher levels of serum UA, but lower eGFR, as well as higher serum sodium and more urine acidity (all p < 0.01). In multivariable analysis, hypertension was an independent predictor of urolithiasis (OR = 2.01, 95% CI 1.30–3.10). Other independent risk factors were high serum uric acid, low urine pH, high dietary salt and low daily water. Conclusion: Hypertension is a strong and independent risk factor for urolithiasis and coexists with metabolic and lifestyle factors that are lithogenic. The addition of stone prevention measures into the control of hypertension might diminish the burden of kidney stones and cardio-renal consequences related to them.